Association of regulatory polymorphisms of gene expression with color phenotypes, water holding capacity, and pH of Nellore meat - Lima, Beatriz Delcarme (2024)
There is a growing demand for high-quality meat, necessitating the assessment of various traits influenced by intrinsic and extrinsic factors. These traits, governed by multiple genes and environmental influences, pose challenges in measurement due to their cost and the need for animal slaughter. Genomics emerges as a promising solution, as a tool to identify genetic markers regulating a significant portion of additive genetic variation in these traits. In this work, we aimed to identify expression quantitative trait loci (eQTLs) associated with meat quality phenotypes in Nellore cattle, including color, water-holding capacity, and pH. For that, we used a comprehensive single nucleotide polymorphisms (SNPs) panel of 553,581 markers, obtained from an imputed panel of SNPs encompassing genotypes from 778 progenies, DNA sequencing from 26 unrelated Nellore sires, and RNA sequencing data from muscle tissues of 192 progenies. The eQTL analysis, using genotypes of 192 animals, revealed 51,324 eQTLs. Subsequent genome-wide association studies (GWAS) with 374 animals identified 838 eQTLs associated with color, 172 with water-holding capacity, and three with pH. Integration with ATAC-Seq peaks identified 75 eQTLs associated with meat color and 24 associated with water-holding capacity in open chromatin regions. Enrichment analysis uncovered pathways such as immune response, antigen processing and presentation, and glutathione metabolism. Notably, most of genes regulated by eQTLs were associated with these pathways. This comprehensive approach identified putative candidate regulatory variants, and genes associated with meat quality, advancing our understanding of Bos indicus genetics.